The Effect of Using Duolingo on English Vocabulary Mastery Among Ninth Grade Students at SMP 16 Medan - Eka Putri Br Tarigan; Kresna Ningsih Manik (Lembaga Yasin AlSys, 2026)
The low mastery of English vocabulary among ninth-grade students at SMP Negeri 16 Medan became the main problem in this study, as reflected in the students’ difficulties in understanding, remembering, and using vocabulary appropriately in communication contexts. This study aims to evaluate the effectiveness of the Duolingo application in improving students’ vocabulary ability. This study employed a quantitative method, with data collected through a pre-test and a post-test, which were then analyzed using SPSS through a paired-samples t-test. The results showed that the students’ mean score increased from 59.87 on the pre-test to 72.57 on the post-test, with a significance value of 0.000, which was lower than 0.05. These findings indicate that the use of the Duolingo application had a significant effect on improving the students’ mastery of English vocabulary. Thus, this study confirms that the use of digital learning media can be an effective alternative for supporting the improvement of students’ vocabulary ability in English language learning.